Mathematical Analysis of an Eco-Epidemic Model with Different Functional Responses of Healthy and Infected Predators on Prey Species - Das, Harekrishna; Shaikh, Absos Ali; Sarwardi, Sahabuddin (Journal of Applied Nonlinear Dynamics, 2026)
This article describes a mathematical model for a predator-prey system with two types of functional responses and a transmissible disease in the predator species. The effect of stocking of healthy predator in healthy predator species class and harvesting of healthy predator are analyzed. The essential mathematical features of the proposed eco-epidemic system such as boundedness, positivity, local and global stability and Hopf bifurcation are discussed. Numerical simulations are also performed to validate the theoretical results obtained.